Oral health status and oral health-related quality of life among a convenience sample of individuals receiving inpatient psychiatric care: a retrospective cross-sectional study - Keeley Flavin; Danna R. Paulson; Mercedes VanDeWiele; Michael Evans; Cyndee Stull (BMC Oral Health)
Abstract Background Those living with mental illnesses have an increased risk of poor oral health exacerbated by lack of motivation for self-care and reduced help-seeking behaviors. Poor oral health status may lead to reduced oral health-related quality of life (OHRQoL) among this population, including the dimensions of Oral Function, Orofacial Pain, Orofacial Appearance, and Psychosocial Impact. Despite this, oral health is often neglected in the management of mental illnesses, particularly in inpatient treatment facilities. The purpose of this research is to investigate the relationship between the oral health status and OHRQoL in adults receiving inpatient psychiatric care. Methods This retrospective, cross-sectional study examined data from medical records of adults between the ages of 18 and 80 receiving inpatient psychiatric care, who had not opted out of research, were English-speaking, and were seen by a hospital dental hygienist between August 1st, 2024 and January 31st, 2025 in response to a consultation request by hospital staff. Oral health status was measured using the Oral Health Assessment Tool (OHAT), and the four dimensions of OHRQoL was measured using the 5-item Oral Health Impact Profile (OHIP-5). Summary scores were analyzed using means and standard deviations. OHAT and OHIP-5 item analysis was completed using frequencies and percentages. Relationships between outcomes were examined using Pearson correlations, with p < 0.05 considered statistically significant. Results Twenty-four patient records met inclusion criteria for analysis. The average time from patient admittance to dental hygiene consult was 17 days, with dental pain being the most common reason for consultation (n = 16). Frequency and percentages showed dental pain, natural teeth, and gums and tissues were most frequently scored as unhealthy on the OHAT assessment. Analysis of OHIP-5 summary scores indicated a mean of (M = 11.17, SD = 6.55), suggesting a moderate average impact on OHRQoL within the sample. Further analysis would be required to determine statistically significant differences or associations. Dental pain was positively correlated with all four dimensions of OHRQoL. No other oral condition was associated with summary or individual items of OHIP-5. Conclusions Results showed generally poor oral health among individuals hospitalized for psychiatric care. OHIP-5 summary scores showed oral health problems were associated with moderate impairment of OHRQoL. Findings emphasize the need for interprofessional preventative care and support oral health integration in psychiatric settings. Future research should incorporate baseline and follow-up oral health assessments to evaluate the impact of targeted oral health interventions on oral health status and OHRQoL.